Analisis Kinerja Karyawan The Kirana Tembok di Kecamatan Tejakula Kabupaten Buleleng Provinsi Bali - Pranata, I Kadek Diva; Rahmawati, Putu Indah (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
This study aims to analyze the performance of The Kirana Tembok employees and the strategies applied to improve the performance of The Kirana Tembok employees. The informants in this study are the manager and 3 employees of each department at The Kirana Tembok. Data collection was carried out by observation, documentation, and interviews with informants. This study uses primary data and secondary data with qualitative descriptive analysis techniques. The results of this study show that employee performance at The Kirana Tembok is good, but not optimal. To overcome these problems, the management of The Kirana Tembok carries out a strategy to improve performance in terms of work quality, namely by providing training or employee training and development, introducing product knowledge, and conducting inspections to other hotels. With this strategy, the management of The Kirana Tembok hopes that employee performance in work quality can improve optimally and achieve the expected goals.